Variability in egg production hormones across four chicken genotypes raised in humid tropical region of Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
Egg production in chickens is influenced by hormonal regulation, which varies across genotypes and environmental conditions. This study examines the reproductive hormonal profiles of four distinct chicken genotypes reared in the humid regions of Nigeria. The genotypes included three indigenous types: normal feather, frizzle feather, and naked neck, and an exotic breed, ISA Brown. A 4 × 2 factorial design laid out in a completely randomized design was adopted, involving 40 chickens, with ten individuals per genotype (5 hens and 5 cocks per genotype). The birds were reared under intensive management conditions, with controlled diets and standardized healthcare practices. Blood samples were collected at 34 weeks of age to analyze key reproductive hormones, including estradiol, progesterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and prolactin, using enzyme-linked immunosorbent assay. Data were analyzed using two-way analysis of variance and hierarchical cluster analysis using average linkage.  Significant means were separated using Duncan multiple range test at a 95% confidence interval. The results demonstrated significant variations (p0.05) across genotypes. The findings suggest that hormonal profiles play a crucial role in influencing egg production patterns, with specific genotypes exhibiting favorable reproductive traits.
Keywords: ISA Brown; Naked Neck; Variability; Prolactin levels